Overview on Italian hemp production chain, related productive and commercial activities and legislative framework - Giupponi, Luca; Leoni, Valeria; Carrer, Matteo; Ceciliani, Giulia; Sala, Stefano; Panseri, Sara; Pavlovic, Radmila; Giorgi, Annamaria (Italian Journal of Agronomy, 2020)
Once a very important crop, the cultivation of hemp has seen a significant reduction in Europe for a long time, but it is now subject to direct payments and promotion initiatives. Italy used to be an important producer and exporter of hemp textiles until the Second World War but currently information is lacking regarding the hemp production chain and legislation on the issue is often misunderstood by producers. Moreover, there has been an important development of economic activities connected with hemp, such as the so-called hemp shops or grow shops and the market of a product called cannabis light, the dried inflorescences of industrial hemp. The aim of the study was to investigate 30 Italian hemp farms in order to identify the characteristics of the production chain and the uses of the crop. Some considerations on this sector in the Italian economic and legislative contest are made and an anonymous web survey on the commercial activities associated with hemp (grow shops) was conducted. Most farms are multifunctional, 83% have been set up recently (in the last ten years) and directly as hemp producers. They are run by young entrepreneurs (57% holders under 35) and allow the use of marginal abandoned territories (43% of the farms). The 30 farms cultivate 460 ha of hemp and the extension of the field crops is very variable, from small patches in the mountains of 0.001 ha to more than 100 ha farms in the plains (in particular in Campania region). Almost all the farms use the crop to produce more than one end-product (seeds, flour, decorticated seeds, hemp-beer, seeds for animal nutrition and food oil from seeds, seeds and inflorescences harvested for cosmetic use, herbal use and extraction of active ingredients). In some cases, technical use linked to selling of the dry top inflorescences of industrial hemp for smoking was declared and it was found that there has been a significant increase in grow shops in Italy, from 4 in 2002 to more than 700 in 2018. As emerges from the analyses of European and Italian legislation, there is a need for clear regulations and a system of control by regulatory organisations considering the actual criticalities. At the same time, the renewed appeal of this crop derives from the multiple possibilities of use of the plant and from growing consumer demand for eco-compatible and sustainable products. Highlights - In the last few years hemp production in Italy is increasing. - In Italy there has been an important development of economic activities connected with hemp. - Regulation and agronomic practices on hemp cultivation in Italy need improvement.